2015
DOI: 10.1152/ajpheart.00339.2015
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine reverses diastolic dysfunction and hypertrophy in familial hypertrophic cardiomyopathy

Abstract: S-glutathionylation of cardiac myosin-binding protein C (cMyBP-C) induces Ca(2+) sensitization and a slowing of cross-bridge kinetics as a result of increased oxidative signaling. Although there is evidence for a role of oxidative stress in disorders associated with hypertrophic cardiomyopathy (HCM), this mechanism is not well understood. We investigated whether oxidative myofilament modifications may be in part responsible for diastolic dysfunction in HCM. We administered N-acetylcysteine (NAC) for 30 days to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 33 publications
6
49
1
Order By: Relevance
“…Similarly, to our findings, NAC also reduced ERK and JNK phosphorylation [14, 46]. The antifibrotic effect of NAC was also observed in other models and organs [46-48].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, to our findings, NAC also reduced ERK and JNK phosphorylation [14, 46]. The antifibrotic effect of NAC was also observed in other models and organs [46-48].…”
Section: Discussionsupporting
confidence: 90%
“…More recently, NAC has been evaluated in experimental models of cardiac injury, particularly hypertrophic cardiomyopathy in which NAC reduced oxidative stress, reversed established cardiac hypertrophy and fibrosis, prevented cardiac systolic and diastolic dysfunction, and improved arrhythmogenic propensity [12, 14, 46]. Similarly, to our findings, NAC also reduced ERK and JNK phosphorylation [14, 46].…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies further indicated that posttranslational modification of cMyBP-C is directly associated with diastolic dysfunction. Oxidative stress-induced S -glutathionylation of cMyBP-C induces Ca 2+ sensitization and a slowing of cross-bridge kinetics, leading to diastolic dysfunction [49, 50]. The phosphorylation of cMyBP-C by PKA and CaMKIIδ [51–53] has been implicated in regulation of diastolic function [19, 54].…”
Section: Discusionmentioning
confidence: 99%
“…Biophysical studies have revealed diverse mutation-induced alterations in sarcomeric protein function, which lead to abnormalities in Ca 2+ handling (7)(8)(9)(10)(11)(12), energy metabolism (13)(14)(15)(16)(17)(18) and/or oxidative stress (19)(20)(21). This has prompted the testing of L-type Ca 2+ channel blockers (e.g., diltiazem) (22,23), angiotensin II receptor antagonists (e.g., losartan) (24), antioxidants (e.g., N-acetylcysteine) (21,25,26), and metabolic modulators (perhexiline) (27) with success in preventing hypertrophy, fibrosis, and adverse cardiac remodeling in animal models. However, neither diltiazem (28), nor losartan (29,30), nor perhexiline (31) is able to prevent development of the cardiac phenotype in HCM patients.…”
Section: Introductionmentioning
confidence: 99%